Utilization of Infographics and Social Media as a Tool for E-Commerce Akad Literacy - Salwa Ade Ramdhani; Muhammad Izzul Islam; Miftahudin (Journal of Islamic Economy and Community Engagement, 2023)
A legal contract between a seller and a buyer that regulates rights and obligations in a sale and purchase transaction is known as a sale and purchase contract. In the context of e-commerce, buying and selling contracts have their own characteristics and challenges because transactions are carried out online without a direct meeting between the seller and the buyer. This service aims to provide more understanding and insight into marketing strategies and consumer behavior in e-commerce, as well as considering related aspects of buying and selling contracts. The method applied in carrying out this activity is the distribution of structured infographics. The results of online literacy activities carried out in the form of distributing infographics and educational feed content on social media indicate that students who actively use social media which are the target of online literacy, from those who previously did not know and understand Islamic finance, eventually gained insight and understanding more related Islamic finance in this case is contracts in e-commerce. The implication of the results of community service in the form of online literacy in the form of infographics and structured educational content is that literacy related to Islamic finance needs to be amplified and disseminated to society so that the impact is that people can know and understand all the advantages and disadvantages of all transactions that they often do in sharia view.